Studi Deskriptif Kesiapan Kerja, Kompetensi Kejuruan, dan Efikasi Diri Siswa SMK Jurusan AKL Pasca Pandemi Covid-19 - Ismoyo, Ananda Gilang; Wahjudi, Eko (Pusat Riset dan Inovasi Nasional, 2023)
Following the Covid-19 pandemic, the competition in Indonesia has become more stringent. The workforce continues to grow, but the number of existing jobs is not yet able to accommodate it. So strategies are needed to face job competition, and in support of job preparedness competence and self-efficiency is required. The purpose of this research is to provide an overview of the conditions of preparedness for work, professional competence and self-efficiency of AKL students that vary in the period after the pandemic in one of the SMK as the research material for achieving the objectives of the establishment of SMK in general and the purpose of the educational unit in particular. This research method uses descriptive quantitative methods with research subjects of students of class XII SMKN Mojoagung major Accounting and Finance Institute of the academic year 2022/2023. The sample size is obtained from the Slovin formula of 105 students.with the technique of sampling using purposive sampler. Data is obtained from a likert scale questionnaire that is scattered and analyzed descriptively for its modular values and then classified according to the categories of each variable. The results of the research obtained that student work readiness in the ready category, professional competence in the good category, and self-efficiency in the high category. Further research is expected to explain the influence or causality relationship of the variables of work readiness, professional competence, and self-efficiency. For AKL SMKN Mojoagung, the results of this research can be used as a reference and evaluation material in order to maintain and enhance the potential of its students.